2018
DOI: 10.1080/15548627.2017.1332567
|View full text |Cite
|
Sign up to set email alerts
|

BNIP3L/NIX-dependent mitophagy regulates cell differentiation via metabolic reprogramming

Abstract: Macroautophagy/autophagy is the process by which cellular components are degraded and recycled within the lysosome. These components include mitochondria, the selective degradation of which is known as mitophagy. Mitochondria are dynamic organelles that constantly adapt their morphology, function, and number to accommodate the metabolic needs of the cell. Extensive metabolic reconfiguration occurs during cell differentiation, when mitochondrial activity increases in most cell types. However, our data demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 0 publications
3
61
0
Order By: Relevance
“…Another study demonstrated that in the first neurons to differentiate in the retina, the mitophagy receptor BNIP3L/NIX increased. These results indicate that mitochondrial dysfunction may play a prominent role …”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that in the first neurons to differentiate in the retina, the mitophagy receptor BNIP3L/NIX increased. These results indicate that mitochondrial dysfunction may play a prominent role …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, nonautophagic mechanisms may also promote mitochondrial removal during reticulocyte maturation . NIX/BNIP3L and BNIP3, which are regulated by hypoxia‐inducible factor (HIF) or forkhead homeobox type O (FOXO), also participate in the hypoxia‐induced mitophagy …”
Section: Mitophagy In Mammalsmentioning
confidence: 99%
“…40 NIX/ BNIP3L and BNIP3, which are regulated by hypoxia-inducible factor (HIF) or forkhead homeobox type O (FOXO), also participate in the hypoxia-induced mitophagy. 41 While the upregulation of NIX or BNIP3 can enhance their activities in mitophagy, the interplay between BNIP3 and LC3 may also act at the level of phosphorylation of BNIP3. When Ser17 and Ser24 adjacent to the LIRs of BNIP3 are phosphorylated, the interplay between BNIP3 and LC3 is enhanced, suggesting a possible role of kinases or phosphatases in regulating mitophagy.…”
Section: Bnip3 and Nix/bnip3l In Mammalian Mitophagymentioning
confidence: 99%
“…Several studies in mice have shown programmed mitophagy is required for RGC differentiation [28,29], and an E50K mutation in the autophagy adaptor protein optineurin (OPTN) has been shown to cause mitochondrial accumulation and RGC death [30]. Additionally, OPTN E50K mutation was also found in the severe form of normal-tension glaucoma (NTG) patients [31].…”
Section: Introductionmentioning
confidence: 99%